"Face(s)" of a PHACE(S) Syndrome Patient before and after Therapy: Particular Case Report and Review of Literature - Maria-Corina Stănciulescu; Florica Ramona Dorobantu; Eugen Sorin Boia; Marius-Călin Popoiu; Simona Cerbu; Rodica Heredea; Emil Radu Iacob; Anca Maria Cimpean; Borislav Dusan Caplar; Anca Voichita Popoiu (MDPI AG, 2022)
A rare, uncommon disorder called PHACE(S) (P-posterior fossa anomalies, H-hemangioma, A-arterial anomalies, C-cardiac anomalies, E-eye anomalies, and S-sternal cleft) of unknown etiology was rarely reported. Children are susceptible to developing PHACE(S) syndrome from the moment they are born. It may be challenging for a physician to appropriately diagnose and treat children with PHACE due to the multifaceted nature of the disease and the extensive range of consequences that may be associated with it. A one-month-old newborn girl was admitted to hospital with extensive, multiple facial infantile hemangiomas, ulceration of the lower lip hemangioma-like lesion, cardiovascular, sternal, and neurological concomitant malformations. Five days following the initial application of the medication, systemic treatment with propranolol and topical treatment with silver sulfadiazine produced their first noticeable benefits. The lip ulceration was mostly healed and facial hemangioma started to regress. The regression continued under therapy and this effect persists for 6 months since Propranolol therapy ended. No cardiovascular or neurological clinical events have been registered during follow-up. The present case has three peculiarities: (1) high number of facial hemangiomas; (2) presence of subependymal cyst not yet reported in the literature associated with PHACE syndrome; and (3) lack of cardiovascular events during therapy knowing that these events frequently appear in PHACE syndrome patients.